FIBER DISRUPTION OF BETUNG BAMBOO (Dendrocalamus asper) BY COMBINED FUNGAL AND MICROWAVE PRETREATMENT - Widya Fatriasari; Wasrin Syafii; Nyoman Wistara; Khaswar Syamsu; Bambang Prasetya; S Heris Anita; Lucky Risanto (BIOTROPIA, 2015)
Combined microwave pretreatment is an effective method to modify carbohydrate and lignin structures of fungal and lignocellulosic materials, thereby improving the hydrolysis process for bioethanol conversion. This study aimed to evaluate the structural changes in carbohydrate and lignin components of betung bamboo following a combined biological–microwave pretreatment. Based on previous findings, a 30-day incubation using 5% and 10% (w/v) inoculum loading of the white-rot fungus Trametes versicolor—which showed the highest delignification selectivity—was selected as the fungal pretreatment. Microwave irradiation was then applied for 5, 10, and 12.5 minutes at 330 W. Characterization of structural changes was conducted using FTIR spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). FTIR analysis revealed that the combined pretreatment affected only the intensity of absorption bands without altering the functional groups. A decline in peak intensity occurred at 1,736 cm⁻¹ (C=O in xylan), 1,373 cm⁻¹ (C–H deformation in cellulose and hemicellulose), 1,165 cm⁻¹ (C–O–C vibration in cellulose and hemicellulose), and 895 cm⁻¹ (β-glycosidic linkage in cellulose). The pretreatment reduced hydrogen bonding in cellulose and weakened lignin–carbohydrate linkages associated with bamboo cellulose crystallinity. A slight increase in crystallinity index was observed due to cleavage of the amorphous fraction. SEM imaging confirmed the disruption of fiber structure, showing increasing degradation with longer microwave exposure durations.